Transcatheter Proximal Coil Blocking with n-Butyl-2-Cyanoacrylate Injection via the Pulmonary Artery Alone for Rasmussen’s Aneurysm - Atsushi Ugajin; Hiroyuki Fujii; Hiroyasu Nakamura; Akifumi Fujita; Takahiro Sasaki; Naoko Mato; Hideharu Sugimoto (Case Reports in Radiology)
Rasmussen’s aneurysm is a peripheral pulmonary artery pseudoaneurysm (PAP) within a tuberculosis cavity. Because it can be perfused from the bronchial and pulmonary arterial circulations, combined embolization via the bronchial and pulmonary arteries is sometimes required. Herein, we present case of a 51-year-old man with Rasmussen’s aneurysm that was successfully treated by proximal coil blocking with n-butyl-2-cyanoacrylate (NBCA) injection via the pulmonary artery alone. With proximal coil blocking, a sufficient amount of NBCA could be injected without unintended reflux of the NBCA cast to the proximal pulmonary artery. To our knowledge, there has been no report that attempted NBCA injection under proximal coil blocking for Rasmussen’s aneurysm. Our treatment approach may be safe and effective for infectious lung disease-related PAP, which has to be treated from the pulmonary artery side.